(untitled) (Third Sector Social Economic Review, 2023)
The Financial Instability Hypothesis is a theory developed by American economist Hyman Minsky. This hypothesis argues that instabilities in the financial sector can lead to economic crises and recessions. According to Minsky, the economic system is inherently unstable, and financial crises occur periodically. Minsky identifies three different stages of the financial system: the hedge stage, the speculative stage, and the Ponzi stage. In the hedge stage, economic agents focus on low-risk investments, with low debt levels. However, over time, economic growth and profit expectations encourage a transition to the speculative stage. In the speculative stage, economic agents engage in risky investments, and debt levels increase. In the Ponzi stage, debt becomes unsustainable, leading to what Minsky calls a ""Minsky Moment."" According to Minsky, financial crises’ fundamental causes are speculation, borrowing, and risk-taking. Optimism in financial markets and increased borrowing can create speculative bubbles that eventually burst. Following crises, adjustments are made in the financial system, but over time, the effect of forgetfulness can lead to the repetition of similar mistakes and the emergence of new crises. Minsky’s Financial Instability Hypothesis emphasizes the significant role played by the financial sector and borrowing in economic cycles. According to this hypothesis, regulatory measures should be taken to maintain financial stability, and the tendency of economic agents to take excessive risks should be limited.